Integration of vibration control and energy harvesting for whole-spacecraft: Experiments and theory. (December 2021) - Xu, Ke-Fan; Zhang, Ye-Wei; Zang, Jian; Niu, Mu-Qing; Chen, Li-Qun
Highlights: A novel vibration control and energy harvesting experimental device is proposed for the whole-spacecraft system. The complexification-averaging (CX-A) method is devoted to analyze the whole-spacecraft system. The experimental and theoretical analysis results show that the NES-GMM device has a positive effect on vibration reduction and energy harvesting. The integration of NES-GMM device causes very little change in the resonance frequency of the whole-spacecraft system. Abstract: Giant magnetostrictive material (GMM) is integrated into a nonlinear energy sink (NES) to construct a NES-GMM device for vibration control and energy harvesting. The NES-GMM device is experimentally embedded in a scaled model of a whole-spacecraft system. LMS Test.Lab software and an oscilloscope are used to collect vibration and energy signals of the whole-spacecraft system with and without the NES-GMM device under sine sweeping frequency excitations. The transmissibility amplitudes, resonant frequencies, and voltage values demonstrate the effeteness of vibration control and energy harvesting of the NES-GMM device under different various conditions. The experimental system is modeled as a two-degrees-of-freedom (2DOF) linear primary system with a nonlinear NES-GMM additional subsystem. The complexification-averaging (CX-A) method verified with numerical verifications is developed to investigate analytically the vibration reduction and energy harvesting of the NES-GMM device for the whole-spacecraft system. The experimental and theoretical results show that the NES-GMM device reduces the vibration and produces the electricity and that the device hardly changes the resonance frequencies of the original whole-spacecraft system. The saddle-node (SN) bifurcation is detected in the steady-state periodic response of the system. The performance of the NES-GMM device is examined for its varying parameters.